Electrocontrolled Liquid Marbles for Rapid Miniaturized Organic Reactions. (20th March 2019) - Liu, Zhou; Yang, Tiyun; Huang, Yuxing; Liu, Yang; Chen, Liucheng; Deng, Libo; Shum, Ho Cheung; Kong, Tiantian
Abstract: Miniaturized droplet reactors hold great promise for the development of green and sustainable chemistry. However, handling liquids with small volumes, especially viscous ones, in a convenient and loss‐free manner remains a challenge. Here, by electrically controlling the coalescence and mixing of particle‐coated droplets, also known as liquid marbles, an effective microreactor is demonstrated for miniaturized chemical reactions involving viscous reagents. By applying an electric voltage to marbles, the induced electromixing of marble microreactors promotes the reaction rate and the product yield. The advantages of electromixed marble reactors are manifested by a series of chemical reactions between aldehydes and 2‐methylindole in viscous glycerol solution. The electrically‐controlled coalescence and mixing establish liquid marbles as microreactors for rapid, efficient, and miniaturized chemical reactions. Abstract : Rapid, versatile, and efficient miniaturized microreactors based on liquid marbles are demonstrated. By tuning the applied voltage, the interior reagents of multiple liquid marbles can be controlled to merge and mix sufficiently. The electroinduced mixing substantially accelerates the reaction rate and increases the reaction yield, even for viscous reagents of small volume in marble microreactors.